Scientific nomenclature of the muscles in the joints of cattle carcass - ANTONOPOULOS (Ι. ΑΝΤΩΝΟΠΟΥΛΟΣ) J. (Journal of the Hellenic Veterinary Medical Society, 2018)
The scientific nomenclature of the muscles in the joints of cattle carcass, as these were defined in the Presidential Decree 186/1981, is mentioned in the present article. The osteal base of the joints, the muscle relations and the origin and insertion of the muscles are also mentioned. The scope of the present article is to juxtapose the scientific name, according to the Nomina Anatomica Veterinaria, next to the trade name of the muscles, solving probable discrepancies about the muscular composition in the joints of catde carcass.